Editorial: Turkish migrants and their descendants in Austria Patterns of exclusion and individual and political responses - Sievers, Wiebke; Ataç, Ilker; Schnell, Philipp (Migration Letters, 2014)
Turkish immigrants and their descendants have become the main target of anti-immigrant political mobilization in Austria since the 1990s. They have come to epitomize the image of the Oriental enemy and the Muslim other. Based on these discursive constructions, Muslims in general, and Turks in particular, have often been described as unwilling to integrate into Austrian society. The articles in this special issue show not only that these discourses and exclusionary attitudes may result in discriminatory practices towards Turkish immigrants and their descendants in Austria, but also that the alleged unwillingness to integrate may be explained by the lack of effort made by the Austrian government and Austrian institutions to integrate this group.